Biological activities of dithiocarbazate schiff base derivatives on normal and diabetic rats / Fathi Farag Mughrabi - Mughrabi, Fathi Farag (Institute of Graduate Studies, UiTM, 2012)
The present study was performed to evaluate the acute toxicity, anti-ulcer, wound healing, antioxidant and antibacterial activities of a Schiff base namely benzyl N’-(indol-3-ylmethylidene)-hydrazinecarbodithioate (BIHC) and its metal complexes, BIHCZn and BIHCNi. The three compounds namely BIHC, BIHCZn and BIHCNi are subsequently collectively referred to as BIHCD. Acute and subchronic toxicity investigation of BIHCD did not show any signs or symptoms of toxicity and all animals remained alive. Blood biochemistry, hematology, and histopathology analysis did not show any significant differences between control and treated groups. BIHCD appears to be safe and no drug-related toxicity was detected even at the highest dose investigated (400mg/kg). Antiulcer activity of BIHCD against ethanol-induced gastric ulcer was studied. Gastric juice was collected for the determination of pH and mucous weight. Grossly, the ulcer control group exhibited severe mucosal injury, whereas pre-treatment with either derivative compounds or Omeprazole resulted in significant protection of gastric mucosal injury. Flattening of gastric mucosal folds was also observed in rats pretreated with BIHCD. Histological studies of the gastric wall of ulcer control group revealed severe damage of gastric mucosa, along with oedema and leucocytes infiltration of the submucosal layer compared to rats pre-treated with either BIHCD or Omeprazole where there were marked gastric protection along with the reduction or absence of oedema and leucocytes infiltration of the submucosal layer. BIHCD and its derivatives promote ulcer protection as ascertained by the comparative decreases in ulcer areas, reduction of oedema and leucocytes infiltration of the submucosal layer. Topical application of BIHC and its metal complexes on the wounds in normal and diabetic rats showed that wound dressed with BIHCD healed significantly earlier than those treated with 10% Tween 20.